Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.11628/ksppe.2021.24.2.179
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Improving the Atmospheric Environment of Classroom for Students' Learning Activities

Abstract: Background and objective: Plant-based biofilter system has become a promising candidate for improving indoor air quality due to its eco-friendly and sustainable nature. However, it remains controversial whether indoor air purification using a biofilter is effective. Methods: This study used the one-group pre-and post-test design to analyze the effects of the operation of the plant-based biofilter system on indoor air quality, students' perception of indoor air quality, health effects, and subjective and object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…In regards to PM removal, unlike potted plants where removal is based solely on deposition on the plant foliage, active systems pull air through a growth medium having many of the same properties as conventional filters. Removal efficiencies for PM in previous studies tend to increase as PM particle size increases (Irga et al 2017a , b ; Kim et al 2021 ; Pettit et al 2017 ). Pettit et al ( 2017 ) found that PM SPRE could be enhanced with appropriate plant species selection, whereby plant species with denser, more complex root systems create a more compact substrate with altered pressure drop properties that positively influence PM removal efficiency.…”
Section: Plants As a Phytoremediation Technologymentioning
confidence: 79%
“…In regards to PM removal, unlike potted plants where removal is based solely on deposition on the plant foliage, active systems pull air through a growth medium having many of the same properties as conventional filters. Removal efficiencies for PM in previous studies tend to increase as PM particle size increases (Irga et al 2017a , b ; Kim et al 2021 ; Pettit et al 2017 ). Pettit et al ( 2017 ) found that PM SPRE could be enhanced with appropriate plant species selection, whereby plant species with denser, more complex root systems create a more compact substrate with altered pressure drop properties that positively influence PM removal efficiency.…”
Section: Plants As a Phytoremediation Technologymentioning
confidence: 79%